Unforeseen Computed Tomography Resimulation for Initial Radiation Planning: Associated Factors and Clinical Impact - April Metzger, MD; Paul Renz, DO; Shaakir Hasan, DO; Stephen Karlovits, MD; Jason Sohn, PhD; Steven Gresswell, MD (Advances in Radiation Oncology, 2019)
Purpose: Repeat computed tomography (CT) simulation is problematic because of additional expense of clinic resources, patient inconvenience, additional radiation exposure, and treatment delay. We investigated the factors and clinical impact of unplanned CT resimulations in our network. Methods and Materials: We used the billing records of 18,170 patients treated at 5 clinics. A total of 213 patients were resimulated before their first treatment. The disease site, location, use of 4-dimensional CT (4DCT), contrast, image fusion, and cause for resimulation were recorded. Odds ratios determined statistical significance. Results: Our total rate of resimulation was 1.2%. Anal/colorectal (P < .001) and head and neck (P < .001) disease sites had higher rates of resimulation. Brain (P = .001) and lung/thorax (P = .008) had lower rates of resimulation. The most common causes for resimulation were setup change (11.7%), change in patient anatomy (9.8%), and rectal filling (8.5%). The resimulation rate for 4DCTs was 3.03% compared with 1.0% for non-4DCTs (P < .001). Median time between simulations was 7 days. Conclusions: The most common sites for resimulation were anal/colorectal and head and neck, largely because of change in setup or changes in anatomy. The 4DCT technique correlated with higher resimulation rates. The resimulation rate was 1.2%, and median treatment delay was 7 days. Further studies are warranted to limit the rate of resimulation.